2023
DOI: 10.3389/fpubh.2023.1285390
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and concerns of emergency medicine practitioners about artificial intelligence in emergency triage management during the pandemic: a national survey-based study

Erhan Ahun,
Ahmet Demir,
Yavuz Yiğit
et al.

Abstract: ObjectiveThere have been continuous discussions over the ethics of using AI in healthcare. We sought to identify the ethical issues and viewpoints of Turkish emergency care doctors about the use of AI during epidemic triage.Materials and methodsTen emergency specialists were initially enlisted for this project, and their responses to open-ended questions about the ethical issues surrounding AI in the emergency room provided valuable information. A 15-question survey was created based on their input and was ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A separate issue being investigated in the survey among emergency physicians is their attitude towards the AI tool. Researchers from Turkey showed that there is a strong conviction among ED staff about the benefits of using AI support to assess a patient during triage; however, concerns about the related ethical aspects of such an intervention are also present among them [ 63 ]. Some of the misunderstandings about the idea of machine learning are addressed by the publications discussing the topic in more depth in the emergency medicine group [ 64 ].…”
Section: Future Of Triagementioning
confidence: 99%
“…A separate issue being investigated in the survey among emergency physicians is their attitude towards the AI tool. Researchers from Turkey showed that there is a strong conviction among ED staff about the benefits of using AI support to assess a patient during triage; however, concerns about the related ethical aspects of such an intervention are also present among them [ 63 ]. Some of the misunderstandings about the idea of machine learning are addressed by the publications discussing the topic in more depth in the emergency medicine group [ 64 ].…”
Section: Future Of Triagementioning
confidence: 99%